Comparative investigation of coherence factor weighting methods for an annular array photoacoustic microscope. (1st July 2022) - Suzuki, Riku; Shintate, Ryo; Ishii, Takuro; Saijo, Yoshifumi
Abstract: To achieve fine visualization of the peripheral microvascular networks, we have developed a photoacoustic (PA) microscope equipped with a four-channel annular array transducer. The quality of PA images processed with delay-and-sum (DAS) method is degraded by off-axis signals. Thus, to achieve higher image quality for the PA microscope, this study evaluated the efficacy of the five coherence factor weighting methods: coherence factor, sign coherence factor, phase coherence factor, circular coherence factor, and vector coherence factor. Using PA signals acquired from a 100 μ m microtube and the skin microvessels, we generated PA images with DAS and one of the weighting methods, and quantitatively evaluated the image quality by calculating the sharpness, contrast ratio, and contrast-to-noise ratio. The results showed the phase coherence factor and the vector coherence factor methods were more effective to clearly visualize the microvascular structure, in terms of vessel sharpening and noise suppression performances, than the other methods.